(untitled) (Journal of Open Law, Technology & Society, 2015)
Despite that the first FOSS licenses were drafted nearly three decades ago, there exists still great confusion even among the experienced technology lawyers and IT professionals as to what are the actual (implied patent) license grants - if any - conferred under the most common FOSS licenses, such as the GPLv2, the BSD license and the MIT license. This article discusses the topic in the light of recent FOSS case litigated in California.